MARKETING STRATEGIES IN INCREASING SALES VOLUME IN MICRO SMALL AND MEDIUM ENTERPRISES FOR TRABAS GEPREK CHICKEN - M.Subhan; Ramadani Kaloko; Khalida Zia Siallagan; Eliya Hazni (RADJA PUBLIKA, 2023)
The aim of this research is to find out and explain the marketing strategy of Ayam Geprek Trabas Micro, Small and Medium Enterprises (UMKM). The research method uses a qualitative approach, data obtained through interviews with MSME owners. The results of the research show that the strategies used are SO strategy, WO strategy, and ST strategy, marketing strategy in the Trabas Geprek Chicken UMKM. The owner is able to create a different sales method from other geprek chicken sellers in general with the quality of the available raw materials, then carry out promotions through social media and the facilities provided are good.